Determinasi dan Respon Stakeholders Terhadap Kinerja Keuangan Pemerintah Daerah - Hanun, Nur Ravita; Hermawan, Sigit; Prapanca, Detak (IAIN Kudus, 2020)
This study deals with local original income as a determinant of district/city finances in the Gerbang Kertosusilo (Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo dan Lamongan) period 2014–2018 and know the responses of the Stakeholders. The research method used is the mix method research. The hypothesis in this study is to explain the influence of tax ratios, retribution ratios, BUMD profit ratios, and other valid income ratios simultaneously, partially and dominantly on the financial performance of regencies or cities in the Gerbang Kertosusilo. To test this hypothesis data analysis tools are used in the form of multiple linear regression. Besides this research also uses a qualitative approach where triangulation techniques will test data collected from interviews, observations and documentation. The results of this study, all variables significantly influence regional financial performance. The stakeholders also justified this. The Financial Performance of Regional Governments reflects the ability of regional heads in managing and maintaining their regions.